On the Urbanization of Poverty - Ravallion, Martin (World Bank, Washington, DC, 2014)
The author identifies conditions under which the urban sector's share of the poor population in a developing country will be a strictly increasing and strictly convex function of its share of the total population. Cross-sectional data afor 39 countries and time-series data for for India are consistent with the expected theoretical relationship. The empirical results imply that the poor urbanize faster than the population as a whole. But the experience across developing countries suggests that a majority of the poor will still live in rural areas long after most people in the developing world live in urban areas.